Textbook of natural medicine - Pizzorno, Joseph E.; Murray, Michael T. (Elsevier, 2013)
Covering preventive, non-invasive, and natural treatments, this title helps you to provide health care that identifies and controls the underlying causes of disease, is supportive of the body's own healing processes, and is considerate of each patient's unique biochemistry.